O número de ouro e construções geométricas - Azevedo, Natália de Carvalho de (2013)
The golden number and its geometry remote from Ancient Greece. The golden number is a real number that can be represented geometrically by dividing a segment in extreme and mean ratio. It is related to the act of determining a point C on a segment AB in order to obtain equal ratios between AB : AC and AC : CB. Its value is obtained by numerical solution of the quadratic equation obtained from this equality. From ruler and compass constructions of the golden mean other geometric constructions are made: triangles, rectangles, pentagons and spirals. The golden number has been present in arts, architecture and nature for years, and it presented in this work as a tool for study, focusing on presentation to high school students.